Analysis of the religious attitudes of children who participate in hadrah art activities in the mushola Al-Fattah, Bulus village, Bandung district, Tulungagung regency - Setiawan, Asep; Pratiwi , Aprianis Eka; Rahmawati , Annisa Testi; Suj’ai , Imam Sukwatus (Universitas Nusantara PGRI Kediri, 2024)
Hadrah in daily life always enlivens in Islamic events such as commemoration of the Prophet's birthday, Tabligh Akbar, Hijriyah New Year celebrations, and commemoration of other Islamic holidays. The aim of this research is to determine the form of religious attitude of children who take part in hadrah art activities and the benefits obtained from the religious attitude of children in the Mushola Al-Fattah, Bulus Village, Bandung District, Tulungagung Regency who take part in hadrah art activities. The type of approach in this research is qualitative which collects data in the form of descriptions because this research aims to explore data from the reality that occurs regarding hadrah art activities. The instruments used to collect data were observation and interview instruments. The results of this research show that the children at the Mushola Al-Fattah have good religious attitudes. These results are known from the results of interviews with art activity trainers in accordance with what was answered by children who took part in hadrah art activities which include doing things sincerely, always praying in an orderly manner, always feeling grateful to Allah SWT, studying religion with the holy book, helpful behavior, as well as deepening and expanding knowledge of beliefs regarding the relationship between humans and God and humans and humans and being able to implement helpful behavior which shows that the form and benefits of the child's religious attitude can be felt. Based on the data above, it can be concluded that the hadrah art activities at the Al-Fattah Prayer Room run well, smoothly and routinely.